Exploring identities through the Internet : Youth experiences online - Maczewski, Metchild (Child and Youth Care ForumChild and Youth Care Forum, 2002)
How do youth experience their online interactions? This article presents youth voices talking about their online experiences and how they perceive these interactions to have influenced their lives highlighting three themes: the notion of “wowness” experiences of freedom, power, and connectedness; and expanding notions of self and identities. It explores how parameters of the Internet (anonymity, interactivity, and connectivity) assist in enabling powerful relations and interactions that benefit some youth very positively. Virtual interactions and online spaces are seen as further sites of interaction in which youth can explore their identities and sense of themselves.
Keywords: identité; jeunesse